2016
DOI: 10.1038/srep36521
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Palladium Supported on Nanoporous Carbon under Anhydrous Condition

Abstract: Due to the high cost of polymer electrolyte fuel cells (PEFCs), replacing platinum (Pt) with some inexpensive metal was carried out. Here, we deposited palladium nanoparticles (Pd-NPs) on nanoporous carbon (NC) after wrapping by poly[2,2′-(2,6-pyridine)-5,5′-bibenzimidazole] (PyPBI) doped with phosphoric acid (PA) and the Pd-NPs size was successfully controlled by varying the weight ratio between Pd precursor and carbon support doped with PA. The membrane electrode assembly (MEA) fabricated from the optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In eq ), j k is the kinetic-limiting current density, j d is the limiting current density, n is the number of transferred electrons in the reaction, F is the Faraday constant (96485.34 C mol –1 ), k is the electron transfer rate constant, C o is the bulk concentration of O 2 in the electrolyte involved (1.2 mM L –1 ) 2 , D o is the diffusion coefficient of O 2 (2 × 10 –5 cm 2 s –1 ), , νis., kinematic viscosity of the electrolyte (1 × 10 –2 cm 2 s –1 ) 2 , and ω is angular velocity in rad/s (2π N , N being the linear rotation speed). ,, Koutecky–Levich plots are shown in Supporting Information Figures S4–S6, and the corresponding n – E dependencies are given in Figure S7. Most of the catalysts present linear relationships between the limiting current density and the rotation rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In eq ), j k is the kinetic-limiting current density, j d is the limiting current density, n is the number of transferred electrons in the reaction, F is the Faraday constant (96485.34 C mol –1 ), k is the electron transfer rate constant, C o is the bulk concentration of O 2 in the electrolyte involved (1.2 mM L –1 ) 2 , D o is the diffusion coefficient of O 2 (2 × 10 –5 cm 2 s –1 ), , νis., kinematic viscosity of the electrolyte (1 × 10 –2 cm 2 s –1 ) 2 , and ω is angular velocity in rad/s (2π N , N being the linear rotation speed). ,, Koutecky–Levich plots are shown in Supporting Information Figures S4–S6, and the corresponding n – E dependencies are given in Figure S7. Most of the catalysts present linear relationships between the limiting current density and the rotation rate.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have proposed electrocatalysts that can carry out more efficient reduction of oxygen to water. These include noble metals (e.g., Pd, Pt, and Au), alloys (e.g., Ag–Co, Ag–Cu, and Pt–Co), ,, iron-based catalysts (e.g., FePSe 3 ), carbon materials (e.g., carbon black and graphene), and quinone (e.g., the anthraquinone process), among others. , These electrocatalysts can be prepared in diverse ways depending on the purpose and materials needed. Several FC studies have reported the modification of the electrode surface with noble metal nanoparticles (NPs) such as Pt, Au, and Pd .…”
Section: Introductionmentioning
confidence: 99%
“…The most significant peak is PdO reduction (0.5-0.8 V vs. RHE), whose coulombic charges are integrated to determine the electrochemical active surface area (ECSA) of the electrocatalysts following the conventional method. [49] The ECSA values of 263.4 and 962.0 cm 2 mg À 1 are estimated for Pd/MOFDC and Pd/SnO 2 /MOFDC, respectively. The oxophilic and spill-over properties of Sn and SnO 2 were verified experimentally with cyclic voltammetry (CV), where the addition Sn@SnO 2 transfer more O species to the Pd electrocatalyst, thereby enhances the PdO reduction peak in the Pd/SnO 2 /MOFDC and requires lower energy than the Pd/MOFDC, as its potential is shifted lower values.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%